BEYOND SELLING: HUMAN MARKETING AS EMPATHETIC COMMUNICATION IN CONTEMPORARY BRAND STRATEGY - Alan Munandar; Syaiful Amin (Jurnal Komunikasi dan Kajian Media, 2026)
Despite extraordinary access to consumer data and marketing tools, companies often fail to establish meaningful emotional connections with their consumers. The study explores the impact of human marketing on true brand-consumer interactions, emphasizing the need of two-way involvement via sympathetic communication. This systematic literature review suggests that transactional marketing prioritizes short-term trades over long-term relationships, contributing to the divide. The synthesis is structured around three themes: (1) neurobiological roots of empathy and emotion, (2) contrasts between transactional and relational perspectives, and (3) customer experience design as a practical representation of empathy across touchpoints. Research indicates that human marketing focuses on perspective-taking, brand vulnerability, and continuous encounters to provide value beyond sales. Emotional connection influences the relationship between empathy and loyalty, while pleasure promotes bonding. Good strategy demands changing from sales emphasis to persistent relationship value generation.